Comparison of Game Situation and Small Side Game in Senior High School on Futsal Learning Skills - Fadri Sidiq; Helmy Firmansyah; Teten Hidayat (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to compare the effectiveness of the Game Situation and Senior high school Sided Games approaches to improving students’ futsal playing skills. The method used is a quasi-experiment with a pretest-posttest control group design. The sample consisted of 32 futsal extracurricular students of senior high school Negeri 1 Lembang who were divided into two groups, each receiving treatment for 12 meetings. The measurement instrument used The Construction Performance Assessment Instrument on Futsal Game Performance which has been validated. The results of the Paired Sample T-Test showed a significant increase in futsal playing skills in both groups. However, the results of the Independent Sample T-Test showed no significant difference between the group using the Game Situation approach and the group using Senior high school Sided Games. These findings indicate that both approaches have relatively equal effectiveness in improving students’ futsal playing skills, both in terms of basic techniques (passing, control, dribbling, shooting) and tactical aspects (decision making, support, and repositioning). The results of this study reference to the development of contextual, active, and fun game-based physical education sports and physical learning strategies.